Cryptography and Blockchain in the Internet of Things: Data Protection through Decentralized Technologies - Yesán Luján, José Alexander (2025)
This article reviewed the use of cryptography and blockchain technologies in the Internet of Things (IoT) for data protection, focusing on decentralized technologies as a secure and efficient solution. The objective was to analyze how the combination of these technologies can enhance the security of IoT devices, ensuring data integrity and privacy. The methodology involved a comprehensive literature review of recent studies on cryptography, blockchain, and their implementation in IoT environments. Various approaches to data decentralization and the implementation of smart contracts in IoT networks were analyzed. The results showed that the application of blockchain and cryptographic techniques significantly strengthens data protection, reducing vulnerabilities in information transmission between connected devices. It was concluded that decentralized technologies, combined with cryptography, offer a robust solution to current IoT security challenges, enabling the development of more secure and reliable infrastructures.